Investigation of changes in crystalline and amorphous structure during deformation of nano-reinforced semi-crystalline polymers by space-resolved synchrotron SAXS and WAXS - Schneider, K; Schoene, A; Jun, T; Korsunsky, A (2009)
Complex structural changes occur in semi-crystalline polymers during deformation. In (nano-)filled systems the situation becomes even more complicated, since not only phase changes may take place, but also local (interfacial) failure between phases may occur. To help identify specific processes taking place within these systems, simultaneous small- and wide-angle X-ray scattering (SAXS/WAXS) measurements were performed using synchrotron radiation during in situ deformation. Using a highly focused beam, spatially resolved local information can be extracted by scanning the beam across the deformed/damaged region within the sample. The characteristic changes in the different phases are presented and discussed. While the study of WAXS patterns gives insight into the orientation and dimensions of the crystallites, SAXS provides information about the mutual arrangement of phases and the interfacial failure phenomena. Based on the analysis of the results obtained in our experiments it will be shown that the first changes in the crystalline phase appear long before macroscopic yielding of the sample is reached, i.e. the onset of irreversible deformation takes place. In the post-yield regime radical changes are observed in both the long- and short-range structures. It is concluded that the presence of nano-fillers exerts a strong influence on the establishment of microcrystalline structure, and hence also on the deformation behaviour at the microscopic scale.